الجزاء الجنائي كوسيلة لتنفيذ الأحكام القضائية الإدارية - نزلي, غنية; شعبان, فضيلة (University of Eloued جامعة الوادي, 2018)
This study looking at the problem of great importance in the field of administrative justice, represented in an indication of the impact of the failure of the criminal sanction against the administration for implementation, exploiting its authority or influence in any form was to stop the execution of the sentence or judicial administrative decision, whether this refrain from direct implementation by the competent abstained, or indirectly, used his power to hinder or delay the execution of the sentence or a judicial decision, with an indication of whether the criminal penalty enough to ensure the implementation of the management of abstaining, the protection of the rights of convicted persons.
الملتقى الدولي الثامن: التوجيهات الحديثة للقضاء الإداري ودوره في إرساء دولة القانون 06-07 مارس 2018 جامعة الوادي
Keywords: الأحكام القضائية الإدارية، مسؤول الإدارة، الإمتناع عن التنفيذ القضاء الإداري; the provisions of the administrative judicial, administration officials, refrain from implementation, the administrative judiciary